Al-Jinrāl Sūdirmān wa Arā’uhu fī al-Difā’ ‘an al-Dawlah al-Jumhūrīyah al-Indūnīsīyah - Nasution, Faruq (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2007)
This article provides biography of the great General Soedirman (born 24 January 1916), one of the key figures in the fight for Indonesia's independence. one of the more interesting aspects of this article is how it looks at Soedirman's youth and education in Muhammadiyah circles. It was Muhammadiyah - or Hizbul Wathan, a scouting organization underneath the umbrella of Muhammadiyah, to be precise - that provided the young Soedirman with critical experience and lessons that were aimed at giving Muhammadiyah youth physical and mental training. Furthermore, particularly in the period of the fight for Independence, this training prepared them for becoming deeply involved in the fight for Indonesia's independence.DOI: 10.15408/sdi.v14i1.563